The development of machine vision and its applications in different industries: A review - Zhang, Lili; Jia, Xiaowei; Chang, Qing; Liu, Xin; Zhang, Zhicheng; Cao, Yanghao; Liu, Junjie; Yang, Yizhao (Mechanical Engineering Advances, 2024)
In recent years, the development of machine vision research is rapid in several areas. In order to promote the better development of machine vision research, it is necessary to clarify its development and application direction. At present, there are few reviews on the application direction of machine vision. This paper sorts out the application of machine vision in various fields, and summarizes the current application status of machine vision from four main functions: recognition, measurement, classification and detection. This paper mainly introduces the improvement of different algorithms of machine vision and its application in medical, agriculture, manufacturing and other industries, providing guidance for the selection of machine vision research direction.